Praktik Higiene Sanitasi dalam Pengelolaan Pangan di Sepuluh Industri Jasa Boga di Kota Bogor - Widiati Purnawita; Winiati Pudji Rahayu; Siti Nurjanah (Institut Pertanian Bogor, 2020)
Catering industry is a food business which produces ready-to-eat food or food that will not be cooked or reheated before serving. Therefore, the safety of food produced by catering industry becomes very important. During period of 2015–2017, the food produced by catering industry was the third largest cause of food borne outbreak in Indonesia. This showed poor compliance level of food hygiene and sanitation in the catering industry, especially during food production. This study was aimed to measure the compliance level of sanitation and hygiene practices during food production in catering industries. This study was carried out in 10 catering industries located in Bogor City, consisting of 2 catering industries in class A2, 4 catering industries in class A3, and 4 catering industries in class B. Data collection was carried out by observation using checklist which was developed from Regulation of The Minister of Health Number 1096 Year 2011. Result showed that catering industries in class A2, A3, and B had an average compliance level of hygiene and sanitation practices during food production. The stage of raw material procurement in class A2 and stage of food processing in class A2, A3, and B were still in poor compliance level of hygiene and sanitation practices that should be more improved. Keywords: catering industries, compliance level, hygiene and sanitation, food production